The ancient Americans - Davis, David R. F. (Colorado : Chariot [production company] ; Illinois : AGC/United Learning [distributor], 1998)
Part one traces the roots of human culture in the New World and explains the emergences of civilization in Mesoamerica. Part two exploresthe civilizations of the highlands of central Mexico-fabulous Teotihuacan and the Toltecs
Editors, David R. F. Davis, Joseph Sitko
Narrator: Lois La Fond
Keywords: America -- Antiquities; Mayas -- Antiquities; Aztecs -- Antiquities